1994
DOI: 10.1089/lps.1994.4.369
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Management of Appendiceal Intussusception Associated with Villous Adenocarcinoma

Abstract: The authors present a case of appendiceal intussusception, a rare finding that can be associated with appendiceal neoplasms. A 74-year-old woman with right lower quadrant abdominal pain was found to have an appendiceal intussusception associated with a villous adenocarcinoma and was managed with a laparoscopic assisted right hemicolectomy. This case is presented along with a review of the symptoms, diagnosis, classification, and appropriate management of this entity via laparoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…50 Other authors have also documented the safety and efficacy of laparoscopic management of AI in the small bowel in the setting of Peutz-Jeghers syndrome as well as in the colon and rectum for management of a sigmoid rectal adenomatous polyp, an appendiceal adenocarcinoma, and a lipoma in the ascending colon. 30,[51][52][53] We propose that in experience hands, laparoscopic management of AI is safe.…”
Section: Discussionmentioning
confidence: 99%
“…50 Other authors have also documented the safety and efficacy of laparoscopic management of AI in the small bowel in the setting of Peutz-Jeghers syndrome as well as in the colon and rectum for management of a sigmoid rectal adenomatous polyp, an appendiceal adenocarcinoma, and a lipoma in the ascending colon. 30,[51][52][53] We propose that in experience hands, laparoscopic management of AI is safe.…”
Section: Discussionmentioning
confidence: 99%
“…A literature search turned up a few cases of appendiceal neoplasm resection via laparoscopy [1,14]. Heller et al [8] reported a small series of appendix carcinoid resections during laparoscopy for gynecologic indications and concluded that this technique was suitable for incidentally discovered appendiceal carcinoid.…”
Section: Discussionmentioning
confidence: 99%
“…Whenever an atypical clinical presentation for acute appendicitis leads the surgeon to entertain a preoperative diagnosis of possible appendiceal neoplasm, the open approach should be preferred. Alternatively, if a preliminary laparoscopic examination of the appendix is suggestive of an appendiceal neoplasm, conversion to an open appendectomy may be the most prudent surgical judgment [14].…”
Section: Discussionmentioning
confidence: 99%
“…Appendiceal intussusception can be secondary to various pathophysiologic lesions, such as polyps (26,27), Peutz–Jeghers syndrome (28,29), mucocele (30), villous adenoma (31,32), mucinous cystadenoma (33–37), adenocarcinoma (38), carcinoid (39), endometriosis (15–24,40–42), fecaliths, helminthiasis, foreign bodies, follicular lymphoid hyperplasia, enteric infections such as adenovirus (43,44), Crohn's disease (45), and cystic fibrosis (5).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical removal of the appendix is the treatment of choice (2). Laparoscopic surgery has been used in management of appendiceal intussusception (38).…”
Section: Discussionmentioning
confidence: 99%